RESPON SISWA DALAM PEMBELAJARAN MATEMATIKA REALISTIK PADA TOPIK FUNGSI DI KELAS II SMPK SANTA AGNES SURABAYA - Haniek Sri Partini (Universitas Negeri Yogyakarta, 2008)
The aim of this study was to know the students’ responses forlearning mathematics by using the realistic approach. Suchstudents’ responses were important as reference for follow up in theimplementation of mathematics realistic education applied atschool. The study was descriptive research. The subjects of thestudy were students of Year 2, Santa Agnes Junior High School inSurabaya. Data were obtained by observing the teacher’scompetence in managing instruction, observing students activities,an achievement test, and a student questionnaire. The researchresulst showed that, out of a total of 53 students, more than 75%gave positive responses on the approach. They further showed that:(1) the students liked all of the learning components (83, 02%), (2)The students considered that all of the learning components werenew things (79, 24%), (3) the students had a great interest to jointhe learning through the realistic approach (88, 68%), and (4) thestudents considered that the student books and student worksheetswere understandable and interesting (83, 96%)